REINTERPRETASI MAKNA JIHAD (STUDI PEMIKIRAN YUSUF QARDHAWI) - Mohamad Rana (UIN Siber Syekh Nurjati Cirebon, 2017)
AbstractJihad as one of the Islamic Shari'ah is often misunderstood by both Muslims and non-Muslims. For most Muslims, interpreting jihad is only a form of struggle to take up arms against the unbelievers. As for the non-Muslims, jihad justification for imaging Islam as a religion of violence and terrorism. The bad imagery arose from a series of violations committed by certain groups of people in the name of jihad and the number of victims who fell due to these actions further confuse the image of Islam in the view of non-Muslims.Yusuf Qardhawi, one of the contemporary moderate scholars, attempted to counter the term jihad which has been understood by the majority of Muslims as a war arming against infidels. In his view the meaning of jihad must be restored to its basic meaning, which is not only meaningful of war. That way, jihad will have a wide scope and it is in line with the initial goal of the tasyri 'jihad itself as the shari'a wishes. Thus, reducing the meaning of jihad which means only war does not match the original purpose of the jihad command itself.Keyword: Jihad, war, Yusuf Qardhawi AbstrakJihad sebagai salah satu syari’at Islam seringkali disalah pahami baik kalangan Muslim maupun non Muslim. Bagi sebagian besar umat Islam, memaknai jihad hanya sebagai bentuk perjuangan mengangkat senjata untuk melawan orang-orang kafir. Sedangkan bagi kalangan non muslim, jihad dijadikan justifikasi untuk mencitrakan Islam sebagai agama kekerasan dan teroris. Pencitraan buruk tersebut muncul akibat serangkaian kekerasan yang dilakukan oleh oknum kelompok tertentu dengan mengatasnamakan jihad dan banyaknya korban yang berjatuhan akibat tindakan tersebut semakin memperkeruh citra Islam dalam pandangan non muslim.Yusuf Qardhawi salah satu ulama moderat kontemporer berusaha melakukan counter terhadap terma jihad yang selama ini dipahami oleh mayoritas umat Islam sebagai perang mengangkat senjata melawan orang kafir. Dalam pandangannya makna jihad harus dikembalikan pada makna dasarnya, yang tidak hanya bermakna perang. Dengan begitu, jihad akan memiliki cakupan luas dan hal tersebut sesuai tujuan awal dari tasyri’ jihad itu sendiri sebagaimana yang dikehendaki syari’ah. Dengan demikian, pereduksian makna jihad yang hanya bermakna perang tidak sesuai dengan tujuan awal dari perintah jihad itu sendiri.Kata Kunci: Jihad, Perang, Yusuf Qardhawi